USP 25 The United States Pharmacepeia. NF 20 National Formulary
1: Supplement U.S. Pharmacopeia and National Formulary. Pages: 2677-2836. Official: April 1, 2002. 2: Supplement U.S. Pharmacopeia and National Formulary. Pages 2837-2955 Official: August 1, 2002.